Lumbrical muscle tear: clinical presentation, imaging findings and outcome - Lutter, Christoph; Schweizer, Andreas; Roemer, Frank; Bayer, Thomas; Schöffl, Volker (Journal of Hand Surgery-European Volume, 2018)
The incidence of lumbrical muscle tear is increasing due to the popularity of climbing sport. We reviewed data from 60 consecutive patients with a positive lumbrical stress test, including clinical examination, ultrasound and clinical outcomes in all patients, and magnetic resonance imaging in 12 patients. Fifty-seven patients were climbers. Lumbrical muscle tears were graded according to the severity of clinical and imaging findings as Grade I-III injuries. Eighteen patients had Grade I injuries (microtrauma), 32 had Grade II injuries (muscle fibre disruption) and 10 had Grade III injuries (musculotendinous disruption). The treatment consisted of adapted functional therapy. All patients completely recovered and were able to return to climbing. The healing period in Grade III injuries was significantly longer than in the patients with Grade I or II injuries ( p < 0.001). We recommend evaluation of specific clinical and imaging findings to grade the injuries and to determine suitable therapy. LEVEL OF EVIDENCE: IV.
EVALuna2:36237